2002
DOI: 10.1080/00926230290001448
|View full text |Cite
|
Sign up to set email alerts
|

The Female Sexual Distress Scale (FSDS): Initial Validation of a Standardized Scale for Assessment of Sexually Related Personal Distress in Women

Abstract: Recent consensus-based characterizations of female sexual dysfunction have emphasized personal distress as an essential component of their definition. To assist researchers and clinicians, we developed a new scale, the Female Sexual Distress Scale, to measure sexually related personal distress in women. In this article, we describe the initial stages in the development and validation of this instrument. Three studies involving a total of approximately 500 women were performed to evaluate the reliability and va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
473
2
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 666 publications
(490 citation statements)
references
References 3 publications
10
473
2
5
Order By: Relevance
“…The four-factor pattern also seems to cast at least some doubt upon the clinical value of the aggregated indices of FSD for diagnosis and treatment. In contrast to our findings, Derogatis et al, 25 using a Female Sexual Distress instrument, found a stable unidimensional factor structure with good internal consistency, regardless of whether it included 20 or 12 items.…”
Section: Discussioncontrasting
confidence: 55%
“…The four-factor pattern also seems to cast at least some doubt upon the clinical value of the aggregated indices of FSD for diagnosis and treatment. In contrast to our findings, Derogatis et al, 25 using a Female Sexual Distress instrument, found a stable unidimensional factor structure with good internal consistency, regardless of whether it included 20 or 12 items.…”
Section: Discussioncontrasting
confidence: 55%
“…symptoms of crying, mood swings, depressions etc. after having had sexual intercourse with your partner' (Derogatis et al, 2002). Response options were on a Likert-type scale, ranging from 'never' (1) to 'always' (5) with the supplementary option 'no sexual activity' (0).…”
Section: Methodsmentioning
confidence: 99%
“…Higher scores indicate more sexual distress and score can range from 0 to 52. The FSDS has shown to be valid and reliable [46].…”
Section: Main Outcome Measuresmentioning
confidence: 99%